2016
DOI: 10.1007/978-3-319-44878-7_8
|View full text |Cite
|
Sign up to set email alerts
|

A Boyer-Moore Type Algorithm for Timed Pattern Matching

Abstract: Abstract. The timed pattern matching problem is formulated by Ulus et al. and has been actively studied since, with its evident application in monitoring realtime systems. The problem takes as input a timed word/signal and a timed pattern (specified either by a timed regular expression or by a timed automaton); and it returns the set of those intervals for which the given timed word, when restricted to the interval, matches the given pattern. We contribute a Boyer-Moore type optimization in timed pattern match… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…In [WHS17], we presented an efficient algorithm for online timed pattern matching that employs (an automata-theoretic extension of) skip values from the Franek-Jennings-Smyth (FJS) algorithm for string matching [FJS07]. We showed that our algorithm generally outperforms a brute-force one and our previous BM algorithm [WAH16]: it is twice as fast for some realistic automotive examples. Through our theoretical analysis as well as experiments on memory consumption, our algorithm was shown to be suited for online usage scenarios, too.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In [WHS17], we presented an efficient algorithm for online timed pattern matching that employs (an automata-theoretic extension of) skip values from the Franek-Jennings-Smyth (FJS) algorithm for string matching [FJS07]. We showed that our algorithm generally outperforms a brute-force one and our previous BM algorithm [WAH16]: it is twice as fast for some realistic automotive examples. Through our theoretical analysis as well as experiments on memory consumption, our algorithm was shown to be suited for online usage scenarios, too.…”
Section: Introductionmentioning
confidence: 95%
“…In [WAH16], [WHS17], we introduced a solution to the timed pattern matching problem where the log is given This work is partially supported by the ANR national research program PACS (ANR-14-CE28-0002), by JST ERATO HASUO Metamathematics for Systems Design Project (No. JPMJER1603), and by JSPS Grants-in-Aid No.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in [91] we successfully employed a few constructions for timed automata-originally devised for verification-for the purpose of monitoring real-time behaviors (monitoring can be understood for an oracle for testing). Our orientation towards abstraction (Sect.…”
Section: Testing Rather Than Verificationmentioning
confidence: 99%
“…Monitoring is an important building block of testing frameworks, too, since we need to judge if an execution of a system is erroneous or not. Recent works on real-time monitoring include [55,82,91].…”
Section: Testing Rather Than Verificationmentioning
confidence: 99%
“…This problem can be related to string matching and pattern matching. The timed pattern matching problem was formulated in [UFAM14], with subsequent works varying the setting and improving the technique (e. g., [UFAM16,WAH16,AMNU17,WHS17]). The problem takes as input a log and a specification, and decides where in the log the specification is ⋆ This is the author (and extended) version of the manuscript of the same name published in the proceedings of the 11th Annual NASA Formal Methods Symposium (NFM 2019).…”
Section: Introductionmentioning
confidence: 99%